Comparison of Recurrent Stroke in Patients with First Stroke Ischemic and Hemorrhagic in Soetomo General Academic Hospital Surabaya - Sihotang, Marselia Febriyanti; Ardhi, Mohammad Saiful; Parenrengi, Muhammad Arifin (AKSONA, 2024)
Highlight: The incidence of recurrent stroke in patients with the first stroke of ischemic type was 2.5-fold higher than that of hemorrhagic type, with the majority of recurrent strokes being the same type as the first stroke. Hypertension is the most common modifiable stroke risk factor in both stroke types, and in 5% of cases, secondary prevention is still not optimal. The average length of hospital stay for patients with the first stroke of hemorrhagic type was 3 days longer, along with a higher average NIHSS score on presentation than patients with ischemic stroke.   ABSTRACT Introduction: Stroke is the leading cause of mortality and disability in Indonesia, as well as being the major cause of death and disability-adjusted life years (DALY) lost worldwide. Recurrent stroke is one of the most common complications of stroke after discharge, despite being highly preventable. Objective: This study aimed to compare the differences in recurrent stroke profiles between patients with first stroke ischemic and hemorrhagic strokes. Methods: The study was done by collecting secondary data from medical records and the stroke registry at Dr. Seotomo General Academic Hospital over a period of six months (January–July 2020). Result: This study examined 36 samples that met the inclusion criteria. The results revealed that patients who experienced their first stroke of the ischemic type had a 2.5-fold higher incidence of recurrent stroke than those who suffered a hemorrhagic type. Except for one case, the majority of patients had the same type of stroke as the first. The most frequent modifiable risk factors seen in these two types of strokes are hypertension and physical inactivity. It was found that there were still 5% of the risk factors for which secondary prevention had not been carried out optimally with antidyslipidemic, antidiabetic, or antihypertensive drugs. The most common acute treatment for ischemic stroke is antiplatelet therapy, either single or dual therapy. Up to 90% of hemorrhagic strokes were treated conservatively, and in one patient, extraventricular drainage was performed. Conclusion: There were more stroke patients with a first stroke of hemorrhagic type that presented with NIHSS scores in the severe to very severe range, and the average length of hospitalization in this group was longer.